Cardiopulmonary resuscitation for in-hospital events in the emergency department: A comparison of adult and pediatric outcomes and care processes. (July 2015) - Donoghue, Aaron J.; Abella, Benjamin S.; Merchant, Raina; Praestgaard, Amy; Topjian, Alexis; Berg, Robert; Nadkarni, Vinay; ,
Abstract: Objectives: To compare outcomes from in-hospital cardiopulmonary resuscitation (CPR) in the emergency department (ED) for pediatric and adult patients and to identify factors associated with differences in outcomes between children and adults. Methods: Retrospective analysis of the Get With The Guidelines – Resuscitation database from January 1, 2000 to September 30, 2010. All patients with CPR initiated in the ED requiring chest compressions for ≥2 min were eligible; trauma patients were excluded. Patients were divided into children (<18 yo) and adults (≥18 yo). Patient, event, treatment, and hospital factors were analyzed for association with outcomes. Univariate analysis was performed comparing children and adults. Multivariate analysis was used to determine factors associated with outcomes. Results: 16, 834 events occurred in 608 centers (16, 245 adult, 537 pediatric). Adults had more frequent return of spontaneous circulation (53% vs 47%, p = 0.02), 24 h survival (35% vs 30%, p = 0.02), and survival to discharge (23% vs 20%, p = NS) than children. Children were less frequently monitored (62% vs 82%) or witnessed (79% vs 88%), had longer duration (24 m vs 17 m), more epinephrine doses (3 vs 2), and more frequent intubation attempts (64% vs 55%) than adults. There were no differences in time to compressions, vasopressor administration, or defibrillation between children and adults. On multivariate analysis, age had no association with outcomes. Conclusions: Survival following CPR in the ED is similar for adults and children. While univariate differences exist between children and adults, neither age nor specific processes of care are independently associated with outcomes.